RIL Skidding Techniques to Improve Productivity and Minimize Production Cost and Environmental Damage (A Case Study at PT Inhutani II Malinau) - Suhartana, Sona; Yuniawati, (Jurnal Penelitian Kehutanan Wallacea, 2019)
Conventional skidding techniques applied in natural forests often bring low productivity, high skidding cost, residual stands damage, and soil damage. RIL’s (Reduced Impact Logging) skidding techniques with better performance and more environmentally friendly should be introduced. This study aims to determine the effect of RIL’s skidding techniques on skidding productivity, skidding production-cost, and environmental damages that comprised residual stands and soil inside natural forests. This research was conducted in November-December 2015 at the site of natural production forest administered by PT. Inhutani II (Indonesia’s State Forest Company), in North Kalimantan. The acquired field data, which consisted of productivity, skidding cost, and damages of residual stands and of soil, were each processed into tabulation forms and then calculated for their averages. The results showed that applying RIL techniques could obtain: 1) The average skidding productivity reached 15.070 m3/hour; 2) The average skidding-production cost was IDR 48,883.45/m3; 3) The skidded-timber volume and skidding duration correlated with the average of skidding productivity, with coefficient of determination of 96.4%; 4) The average damage on residual stand due to skidding was 17.10% including canopy damage (12.5%), broken stems (37.5%), stem injury (12.5%), and leaning trees (37.5%), 5). Average soil depth and soil volume due to the topsoil displacement were 0.047 m and 3.726 m3/m; and 6) the use of matting strips can reduce the occurrence of soil damage during skidding.